Emerging and re-emerging infectious disease threats in South Asia: status, vulnerability, preparedness, and outlook. (11th April 2017) - Laxminarayan, Ramanan; Kakkar, Manish; Horby, Peter; Malavige, Gathsaurie Neelika; Basnyat, Buddha
Abstract : Without investment in surveillance and early detection the region remains vulnerable to infectious disease threats, say Buddha Basnyat and colleagues